Surgical Time Evaluation of Traditional and Laparoscopic Unilateral Ovariectomy in Jennies - Rabab Samir Karkar; Sinan Adnan al-khazraji (مجلة الانبار للعلوم البيطرية)
Surgeries are strenuous for the animal patient regardless of the procedure type. This study aimed to compare the surgical time that required to perform a traditional ovariectomy vs a laparoscopic ovariectomy. To achieve this; ten adult Jennies were divided equally into two groups, group A underwent ovarian lift by traditional surgery, while group B got an ovarian lift by laparoscopy. Surgical time evaluated from the scalpel incision till the last suture stitch. The finding showed a significant differences at the level of (P≤0.01) between the two groups, traditional ovariectomy group took from 50 to 70 minutes, while the laparoscopic group took from 120 to 158 minutes. In conclusion the duration of Jenny's laparoscopic ovariectomy operation is greater than that of the traditional ovariectomy surgery, and it gets shorter as additional surgeries are performed.